Assessing cross-national inequalities and predictive trends in gout burden: a global perspective (1990–2021) - Mingyang Li; Qilong Nie; Qilin Xia; Zeping Jiang; Zeping Jiang (Frontiers in Medicine)
BackgroundGout, caused by hyperuricemia and the deposition of monosodium urate crystals in joints, remains a major global health issue. Despite progress in treatment, its prevalence continues to rise, contributing to comorbidities like cardiovascular and chronic kidney diseases. Understanding global trends and sociodemographic disparities is crucial for developing targeted interventions.MethodsWe analyzed gout prevalence, incidence, and disability-adjusted life years (DALYs) from 1990 to 2021, stratified by age, sex, and economic development. Decomposition analysis quantified the impact of demographic factors, while advanced analysis assessed the relationship between gout burden and socioeconomic development. Prediction models forecasted future trends, and cross-national inequalities were evaluated to highlight disparities across regions with different development levels.ResultsBetween 1990 and 2021, the global prevalence of gout increased from 22,264,515 (95% UI: 17,793,190–27,965,605) to 56,474,572 (95% UI: 45,161,987–70,288,316), with the age-standardized prevalence rate (ASPR) rising from 536.54 to 653.82 per 100,000 population [(Estimated annual percentage changes) EAPC: 0.87%, 95% CI: 0.80–0.95]. The incidence of gout cases increased by 136.1%, with the age-standardized incidence rate (ASIR) rising by 17.12% over this period. Similarly, the age-standardized death rate (ASDR) grew by 21.30%, accompanied by a substantial increase in DALYs. Decomposition analysis revealed that aging significantly contributed to increased gout prevalence in Middle SDI regions (36.79%), while population growth was the dominant factor in Low SDI regions (98.58%). Advanced analysis indicated substantial gaps between observed gout burden and optimal levels in high-SDI countries, such as the United States and Australia, highlighting unrealized opportunities for improving outcomes. Prediction analysis projected a stable global burden of gout from 2021 to 2045, with notable gender-specific and age-specific trends. Cross-national inequality analysis showed worsening disparities in gout prevalence, incidence, and DALYs between high- and low-SDI regions, reflected in increasing Slope Index of Inequality and Health Concentration Index values from 1990 to 2021.ConclusionThe global burden of gout has risen, with high-SDI regions facing risks from lifestyle changes and obesity, while low-SDI regions struggle with healthcare access. Public health strategies should focus on modifiable risk factors, healthcare infrastructure, and gender- and age-specific trends to address disparities.